Radiofrequency catheter ablation for atrial flutter following orthotopic heart transplantation. Issue 4 (1st April 1998) - Pitt, M P I; Bonser, R S; Griffith, M J
Abstract : A 26 year old woman with a diagnosis of limb girdle muscular dystrophy and peripartum cardiomyopathy underwent orthotopic heart transplantation using standard atrial anastomoses. Recurrent atrial flutter was demonstrated in the absence of histological evidence of cellular rejection. Radiofrequency ablation of the flutter circuit was successfully performed allowing the avoidance of long term antiarrhythmic therapy. Ten weeks following ablation and cessation of amiodarone, presyncopal symptoms were found, associated with daytime and nocturnal sinus pauses of 2.9 seconds and 4.2 seconds, respectively. There was no evidence of AV node conduction impairment. In view of the continued absence of cellular rejection and the evident denervated state of the heart, the pauses reflected significant donor sinus node dysfunction; therefore, an AAIR permanent pacing system was implanted. At the time of pacemaker implantation atrial pacing at 150 beats/min did not produce significant PR interval prolongation or AV block. This case serves to advise rigorous follow up in such patients to continue to seek evidence of sinus node dysfunction potentially requiring permanent pacemaker implantation.